Intertwined Messages: Aesthetic and Didactic Aspects of Dual-Language Sámi Picturebooks - Palo, Annbritt; Manderstedt, Lena; Bjuhr, Åsa (Barnboken, 2025)
Theme: Multilingualism and Children's Literature. Ill. Henry Lyman Saÿen - Child Reading (1915–1918). Smithsonian American Art Museum, object number1968.19.11. This article focuses on aesthetic and didactic aspects of literary multilingualism and the interaction between these aspects in two contemporary dual-language picturebooks with Sámi motifs and characters. Lilli, áddjá, ja guovssahas/Lilli, farfar och norrskenet (Lilly, Grandpa and the Northern Lights, 2020), written by Elin Marakatt and illustrated by Anita Midbjer, and Gájuoh muv! Gïjrra Almien jah Enoken luvnnie/Rädda mig: Vår hos Almmie och Enok (Save me: Spring at Almmie and Enok’s, 2021), written by Sophia Rehnfjell and illustrated by Inga-Wiktoria Påve, are intended for 3–7-year-olds and combine a Sámi language and Swedish. The analyses show the aesthetic and didactic interplay between verbal and visual elements. The insertion of North Sámi words in an otherwise Swedish text can highlight culture, traditional beliefs, and history, and the Ume Sámi glossaries can be used to talk about the illustrations and learn words pertaining to reindeer husbandry and life in Sápmi. The vocabulary has a didactic function, while the literary text and the illustrations tell stories about the Sámi peoples, thus being both aesthetic and didactic. Literary multilingualism is teamed with didactics and Sámi aesthetics to support language acquisition, to depict and to make visible Sámi culture and Sámi peoples to in-group as well as out-group readers.